The geology of the Blouberg Formation, Waterberg and Soutpansberg Groups in the area of Blouberg Mountain, Northern Province, South Africa - Eriksson, Patrick George (University of Pretoria, 2013)
Thesis (DPhil (Geology))--University of Pretoria, 2000.